SELF RELIANT INDIA A ROLE OF MANUFACTURING AND ITS EFFECT ON EMPLOYMENT GENERATION IN MAKING INDIA - Jyani, Mukesh; Satsangi, Priya (International Journal of Research -GRANTHAALAYAH, 2025)
The manufacturing sector stands as a fundamental pillar of economic growth and industrial advancement across the world. It performs the vital task of converting raw materials into finished goods while simultaneously generating employment, enhancing exports, and encouraging innovation. Acting as a connecting link between the agricultural and service sectors, manufacturing fosters large-scale industrialization, promotes self-reliance, and contributes to the sustainable progress of a nation. This research paper discusses the broad economic significance of the manufacturing sector, emphasizing its impact on GDP, employment, trade, and technological development. It further highlights how the integration of digitalization and advanced manufacturing under the industry 4.0 framework is redefining global economic systems. The paper also identifies current challenges, supportive policy frameworks, and evolving trends that influence the future contribution of manufacturing to economic prosperity.